Thoracoscopic Esophagectomy for a Huge Leiomyosarcoma - Manipadam, John Mathew; Bains, Satinder Pal Singh; Mahesh, S.; Emmanuel, Ami Maria; Ramesh, H. (The Surgery Journal, 2019)
Esophageal leiomyosarcoma is the commonest of all esophageal sarcomas but yet has a very low incidence. These tumors have been resected by the open approach so far. We describe the steps and challenges involved in the thoracoscopic excision of a huge leiomyosarcoma of the esophagus.
Keywords: leiomyosarcoma of esophagus; thoracoscopic esophagectomy; minimally invasive esophagectomy